Influence of Hypotermia on Intensity of Oxidative Modification of Ground Squirrels’ Blood Plasma Proteins - Astaeva, M. D.; Abdullaev, V. D.; Klichkhanov, N. K. (Problems of Cryobiology and Cryomedicine, 2009)
The effect of artificial hypothermia of various depths on intensity of oxidative modification of plasma proteins and activity of antioxidant system of ground squirrel blood during active summer time were studied. It has been shown that hypothermia at 20 and 10°C differently affects the intensity of oxidative modification of plasma proteins. Under hypothermia independently of its depth the increase of protein resistance of blood plasma to oxidants has been revealed. At low temperatures of body the significant increase of hydrophil antioxidants’ activity in blood plasma is found that may play an important role in protection of proteins from oxidative damage.